Understanding value in a healthcare setting: An application of the business model canvas. Issue 3 (October 2021) - Sibalija, Jovana; Barrett, David; Subasri, Mathushan; Bitacola, Lisa; Kim, Richard B
The business model canvas is a popular tool used to develop value-driven business models. Specific emphasis is placed on understanding what customers value and providing users with steps on how to design and deliver value for their customers. In health care, creating and delivering value for patients is an often-discussed topic, with the provision of patient-centered care becoming a standard for many health care organizations. While patients play a key role in determining value, providers are the key to delivering value. Therefore, effective health care management relies on integrating multiple perspectives from key stakeholders. This process requires consideration of the key needs that must be addressed, the resources and capabilities necessary to meet these needs, and the interests and values specific to each set of stakeholders. The business model canvas lends itself well to health care service planning as it incorporates the factors described above into the business model's conceptualization and subsequent realization. This article outlines how the business model canvas was applied to assess the needs of physician stakeholders to help guide the expansion of a pharmacogenomic-based precision medicine clinic that conducts genetic testing for patients at risk of experiencing adverse drug reactions. The article provides a detailed description of how the business model canvas was used and adapted to understand physician's responsibilities and challenges related to drug prescription and dosing, and how the clinic could address physician needs and create value by mapping clinic services onto physician needs and wants. Interviews were conducted with physicians and the data were analyzed following the recommendations of the developers of the business model canvas. The article examines the strengths and limitations of the business model canvas and discusses its applicability to a health care setting.